The Evolution of Montreal's Precipitation: Climate - Leduc, Richard (Université McGill, 1977)
Keywords: Climat

Climate and Architecture: With Special Reference to Montreal and Surroundings - Aronin, Jeffrey Ellis (Université McGill, 1951)
Keywords: Climat

La prise en compte de l’adaptation au changement climatique dans les politiques publiques de verdissement (2005-2015) : le cas de Montréal - Vachon, Jérémie (Université de Montréal, 2016)
Keywords: Climat

Enjeux et dynamiques de la mise en œuvre de stratégies d'adaptation aux changements climatiques en milieu urbain: les cas de Montréal et Paris - Simonet, Guillaume (Université du Québec à Montréal, 2011)
Keywords: Climat

Recherche ou lobbyisme ? L’Institut économique de Montréal et le réchauffement climatique depuis 1999 - Lamy, Guillaume (Politique et Sociétés, 2022)
Keywords: Climat; Libéralisme

L'état de préparation des intervenants de l'Île de Montréal en l'an 2000 face à des pluies diluviennes comme celles du 14 juillet 1987 - Boissonneau, Julie (Université de Sherbrooke, 2001)
Keywords: Climat

Movement, Morphology and Circulation of Montreal Summer Storms - Shaw, Roderick (Université McGill, 1970)
Keywords: Climat

Une étude bioclimatique de la ville de Montréal - Lafleur, Daniel (Université McGill, 1972)
Keywords: Climat

Hauteur-fréquence-durée des précipitations dans la région de Montréal - Sylvestre, Gilbert (Université Laval, 1967)
Keywords: Climat

Description du contenu pollinique de l'atmosphère de Montréal et de Québec pour les années 1983 et 1984 - Durand, Louise (Université de Montréal, 1986)
Keywords: Climat

Dynamics of Heavy Warm Season Precipitation Events in Montréal - Dookhie, Giselle C. (Université McGill, 2011)
Keywords: Climat

A Synoptic Climatology of Ground-Level Ozone for Montreal, Quebec - Stephens, Kate (Université McGill, 1995)
Keywords: Climat

A Synoptic Climatology of Montreal Precipitation - Fischer, Alexander P. (Université McGill, 1998)
Keywords: Climat

Freezing Rain in the Montreal Area - Leech, Margaret E. (Université McGill, 1978)
Keywords: Climat

Planetary and Synoptic-Scale Analysis of Freezing Rain Events in Montreal, Quebec - Ressler, Gina (Université McGill, 2010)
Keywords: Climat

Effets du dioxyde d'azote et de l'ozone sur les maladies respiratoires à Montréal - Caouette, Chantal (Institut national de la recherche scientifique - Centre Eau Terre Environnement, 2010)
Keywords: Climat; Pollution

Étude de l'hivernité urbaine, analyse d'un récit de construction identitaire montréalais - Myriam, Guillemette (Université du Québec à Montréal, 2020)
Keywords: Carnaval; Climat; Espace souterrain

Montréal et son environnement naturel - Perron, Normand (Histoire de Montréal et de sa région, 2012)
Keywords: Climat; Géographie physique; Voie maritime

La réduction de gaz à effet de serre et les transports urbains des personnes à Montréal - Gandulfo, Mónica (Université de Sherbrooke, 2000)
Keywords: Automobile; Climat; Transport en commun

Montreal and Its Natural Environment - Perron, Normand (Montreal: The History of A North American City, 2018)
Keywords: Climat; Géographie physique; Voie maritime

"Le Canada est un païs de bois": Forest Resources and Shipbuilding in New France, 1660-1760 - Delaney, Monique (Université McGill, 2003)
The colonial contribution to the French naval shipbuilding industry in the seventeenth and eighteenth centuries, explored within the context of the forest from which the resources for the industry were taken, was a remarkably successful venture that came to an end with the onset of war. In the past, the end of the French naval shipbuilding industry in New France has been attributed to the action or inaction of France that resulted in the inefficient use of forest resources. Issues of interest in, organization or support of colonial efforts by France, however, were nevertheless, limited by the immutable realities of the colonial forest environment. This thesis argues that the success of the industry, considered within the appropriate context, is a consequence of colonial persistence in the face of constraints imposed by the colonial forest environment---despite these other significant issues. The official correspondence, written by colonial officials in New France, record colonial efforts to supply France with timber and detail the development of a naval shipbuilding industry in the colony. These documents provide source material for a case study that demonstrates the constraints imposed by the colonial forests on the experience of colonists, timber suppliers and shipbuilders. The colonial forest was not the same as the forests in France. A simple transfer of knowledge and practice from one forest to another was insufficient to deal with the differences in climate, forest age, tree species and the extent to which human activity affected the different forests. These differences challenged the way in which colonists could use forest resources for their own needs, for export to France and for naval construction. To consider this use of resources, without considering the differences between the available materials in the colony and those available in France, is to look at the story removed from the setting in which it took place. The unique forest in the colony was the setting in which colonial shipbuilding took place. Any study of the development of this industry, or any other industry that relied on forest resources, must give consideration to the constraints and realities of that forest.
Keywords: Construction navale